Data, matter, design : strategies in computational design - Melendez, Frank (Frank P.); Diniz, Nancy; Del Signore, Marcella (New York, NY : Routledge, 2021)
"Data, Matter, Design presents a comprehensive overview of current design processes that rely on the input of data and use of computational design strategies, and their relationship to an array of physical outputs. Technological changes, through the use of computational tools and processes, have radically altered and influenced our relationship to cities and the methods in which we design architecture, urban, and landscape systems. This book presents a wide range of curated projects and contributed texts by leading architects and designers that transform data as an abstraction, into spatial, experiential, and performative configurations within urban design, emerging materials, robotics, responsive and adaptive systems, and virtual/augmented/mixed reality. Richly illustrated with over 200 images, Data, Matter, Design is an essential read for students, academics, and professionals to evaluate and discuss how data in design methodologies and theoretical discourses have evolved in the last two decades and why processes of data collection, measurement, quantification, simulation, algorithmic control, and their integration into methods of reading and producing spatial conditions, are becoming vital in academic and industry practices"--
Data + urban design -- Data + emerging materials -- Data + robotics -- Data + response and interaction -- Data + VR, AR, MR, XR and scanning technologies -- Futures for data and design.
OCLC-licensed vendor bibliographic record.
Keywords: Design and technology; Technology -- Social aspects; ARCHITECTURE / General; ARCHITECTURE / Design & Drafting